Manajemen penyaluran dana dalam bantuan bencana banjir dan longsor di daerah Maninjau Kecamatan Tanjung Raya Kabupaten Agam oleh Masyarakat Tualang Peduli - Nabilla, Nabilla (Maliki Interdisciplinary Journal, 2023)
Disasters are inevitable occurrences. Various forms of assistance are greatly needed for victims of natural disasters. This article discusses the management of fund distribution in the context of disaster relief efforts for flood and landslide victims in the Maninjau region by the Tualang Peduli Community. Within this article, i tis explained how this community responds to disasters with effective fundraising strategies and organized distribution. This research employs a qualitative approach method. Data is gathered through interviews and also from literature sources such as journals, books, and articles related to disaster fund distribution management. This study serves as a real-life example that provides insights into how a community can effectively and efficiently respond to disasters.